Breakfast and psychosocial behavioural problems in young population: The role of status, place, and habits - López-Gil, José Francisco; Smith, Lee; López-Bueno, Rubén; Tárraga-López, Pedro Juan (Frontiers in Nutrition, 2022)
The aim of this study was to examine whether breakfast status, place and habits are associated with psychosocial behavioural problems in a nationally representative sample of young people aged 4 to 14 years residing in Spain. This study analysed secondary data from the Spanish National Health Survey (2017), including 3772 Spanish children and adolescents. Breakfast status, place and habits were assessed by ad hoc questions answered by parents/guardians. The Strengths and Difficulties Questionnaire (SDQ) parents' version form was applied to evaluate the psychosocial health of their children. Skipping breakfast and eating breakfast out of home were linked to greater odds of psychosocial behavioural problems (skipping breakfast: OR=3.29; CI 95%, 1.47–7.35; breakfast out of home: OR=2.06; CI 95%, 1.27–3.33) than eating breakfast at home. Similarly, not consuming coffee, milk, tea, chocolate, cocoa, yogurt, etc., for breakfast was related to greater odds of psychosocial behavioural problems (OR=1.76; CI 95%, 1.21–2.55). This association was also found for those who did not eat bread, toast, cereals, pastries, etc., for breakfast (OR=1.31; CI 95%, 1.01– 1.73). Conversely, not consuming eggs, cheese, ham, etc., was associated with lower odds of psychosocial behavioural problems (OR=0.56; CI 95%, 0.38–0.83). Our results show that eating breakfast (specifically at home) and breakfast habits related to the intake of certain food/beverages groups were associated with higher or lower odds of psychosocial behavioural problems.